Knowledge Production and Utilization - Beal, George M.; Meehan, Peter ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
The study of knowledge production and utilization deals with the problems of how to translate theoretical concepts and knowledge into practical solutions to people's problems. Many criticisms have been leveled at aspects of previous information system models, including their linearity, one-way communication paths, overdependence on scientific knowledge, and lack of interactive communication. The six-stage model proposed here attempts to correct these problems. In the scientific knowledge production stage, basic and applied research are carried out. In the knowledge management stage, the resulting findings are monitored, screened, indexed, catalogued, packaged, and stored. In the knowledge translation stage, "linkers" translate the available knowledge into terms applicable to the clients' formulation of their problems. The product development stage contains the development of products having the potential to meet user needs. These products are then distributed to users in the product dissemination stage. In the product adoption and utilization stage, the users adapt and effectively utilize the solution. Although this six-stage model may appear one-way linear, a look at a concrete example of its functioning shows that it is not. Needs can be communicated from users back through disseminators and developers to the knowledge production stage, and interaction may occur between many of the stages. (Author/JM)
ERIC Note: Paper presented at the Annual Meeting of the Rural Sociological Society (San Francisco, California, August 1978); For a related document, see EA 011 561; Not available in paper copy due to marginal legibility of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Action Research; Communication (Thought Transfer); Information Dissemination; Information Utilization; Models; Research Problems; Research Utilization; Rural Areas; Speeches; Knowledge Production and Utilization; Speeches/Meeting Papers; Reports, Descriptive